Expert Opinion on the Management of Growth Hormone Deficiency in Brain Tumor Survivors: Results From an Italian Survey - Di Iorgi, Natascia; Morana, Giovanni; Cappa, Marco; D’Incerti, Ludovico; Garrè, Maria Luisa; Grossi, Armando; Iughetti, Lorenzo; Matarazzo, Patrizia; Parpagnoli, Maria; Pozzobon, Gabriella; Salerno, Mariacarolina; Sardi, Iacopo; et al. (Frontiers in Endocrinology, 2022)
Background: Growth hormone deficiency (GHD) is the first and most common endocrine complication in pediatric brain tumor survivors (BTS). GHD can occur due to the presence of the tumor itself, surgery, or cranial radiotherapy (CRT). Aims: This study aimed to evaluate management and adherence to current guidelines of the Italian centers engaged in the diagnosis and follow-up of GHD patients with BTS. Methods: A multidisciplinary scientific board of pediatric endocrinologists, oncologists and radiologists with neuroimaging expertise discussed and reviewed the main issues relating to the management of GHD in pediatric BTS and developed a survey. The survey included questions relating to organizational aspects, risk factors, diagnosis, definition of stable disease, and treatment. The online survey was sent to an expanded panel of specialists dedicated to the care of pediatric BTS, distributed among the three specialty areas and throughout the country (23 Italian cities and 37 Centers). Results: The online questionnaire was completed by 86.5% (32 out of 37) of the Centers involved. Most had experience in treating these patients, reporting that they follow more than 50 BTS patients per year. Responses were analyzed descriptively and aggregated by physician specialty. Overall, the results of the survey showed some important controversies in real life adherence to the current guidelines, with discrepancies between endocrinologists and oncologists in the definition of risk factors, diagnostic work-up, decision-making processes and safety. Furthermore, there was no agreement on the neuroimaging definition of stable oncological disease and how to manage growth hormone therapy in patients with residual tumor and GHD. Conclusions: The results of the first Italian national survey on the management of GHD in BTS highlighted the difference in management on some important issues. The time to start and stop rhGH treatment represent areas of major uncertainty. The definition of stable disease remains critical and represents a gap in knowledge that must be addressed within the international guidelines in order to improve height, metabolic and quality of life outcomes in cancer survivors with GHD.